Induction of cryptic bioactive 2, 5-diketopiperazines in fungus Penicillium sp. DT-F29 by microbial co-culture. Issue 7 (16th February 2017) - Yu, Liyan; Ding, Wanjing; Wang, Qianqian; Ma, Zhongjun; Xu, Xiaowu; Zhao, Xiaofeng; Chen, Zhe
Abstract: Ten new and 13 known prenylated 2, 5-diketopiperazines (2, 5-DKPs) were identified from co-culture of Penicillium sp. DT-F29 with Bacillus sp. B31. The constitutions and relative configurations of new compounds were established by 1D and 2D NMR spectroscopic data analysis. The isolated 2, 5-DKPs in bioactivity test showed bromodomain-containing protein 4 (BRD4) inhibitory activities, and compound14, with IC50 values of 6.54 μ M, was potential for BRD4 inhibitor discovery. Graphical abstract: